Prefecture government fiscal intervention and corporate asset allocation: The perspective of transaction cost theory - Jieyang Pan (PLoS ONE, 2026)
This study examines the impact of prefecture-level government fiscal intervention on corporate asset allocation in China from the perspective of transaction cost theory. Using a panel dataset of Chinese listed firms from 2008 to 2023, we find that increased fiscal intervention significantly reduces firms’ allocation to operating assets while increasing financial asset holdings, indicating a substitution effect. Mechanism analysis suggests that fiscal intervention raises regional transaction costs, discouraging long-term productive investment. Heterogeneity analysis shows stronger effects among private firms and firms more dependent on local economies. These findings provide new evidence on how government intervention shapes firm-level resource allocation and offer policy implications for improving fiscal efficiency and supporting real-sector development in emerging economies.